2014
DOI: 10.1002/cssc.201402806
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Acceptor‐Dependent Light Absorption, Excited‐State Relaxation, and Charge Generation in Triphenylamine Dye‐Sensitized Solar Cells

Abstract: By choosing a simple triphenylamine electron donor, we herein compare the influence of electron acceptors benzothiadiazole benzoic acid (BTBA) and cyanoacrylic acid (CA), on energy levels, light absorption, and dynamics of excited-state evolution and electron injection. DFT and time-dependent DFT calculations disclosed remarkable intramolecular conformational changes for the excited states of these two donor-acceptor dyes. Photoinduced dihedral angle variation occurs to the triphenylamine unit in the CA dye an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Electron injection into TiO 2 , extensively studied, , ,,, is kinetically complex, a characteristic commonly attributed to hetero­geneities in the oxide. ,,, Electron injection can occur by direct light-driven electron transfer from a donor level on the chromophore to an acceptor level in the semiconductor ,, or, more commonly, from an excited state or states following light absorption. ,,,,,,,, , From the experimental data for −RuP 2+ and its analogues on TiO 2 , the initial electron injection process or processes occur on the hundreds of femtoseconds to hundreds of picoseconds time scale from the initially formed singlet MLCT state(s), TiO 2 |− 1 {[(4,4′-(PO 3 H 2 ) 2 ­bpy – )­Ru III ­(bpy) 2 ] 2+ *}, before 1 MLCT → 3 MLCT internal conversion can occur. Electron injection can also take place from non-thermally equilibrated 3 MLCT states before they undergo vibrational relaxation.…”
Section: Dspec Processesmentioning
confidence: 99%
“…Electron injection into TiO 2 , extensively studied, , ,,, is kinetically complex, a characteristic commonly attributed to hetero­geneities in the oxide. ,,, Electron injection can occur by direct light-driven electron transfer from a donor level on the chromophore to an acceptor level in the semiconductor ,, or, more commonly, from an excited state or states following light absorption. ,,,,,,,, , From the experimental data for −RuP 2+ and its analogues on TiO 2 , the initial electron injection process or processes occur on the hundreds of femtoseconds to hundreds of picoseconds time scale from the initially formed singlet MLCT state(s), TiO 2 |− 1 {[(4,4′-(PO 3 H 2 ) 2 ­bpy – )­Ru III ­(bpy) 2 ] 2+ *}, before 1 MLCT → 3 MLCT internal conversion can occur. Electron injection can also take place from non-thermally equilibrated 3 MLCT states before they undergo vibrational relaxation.…”
Section: Dspec Processesmentioning
confidence: 99%
“…Thus far, highly efficient silicon or PSCs usually show an E Loss as low as 0.4–0.5 eV, and the recent boost in PCEs of OSCs based on non‐fullerene acceptors can be also attributed to the continuous reduction in E Loss . However, a much larger E Loss can be observed in DSSCs, which usually originates from the undesired loss of energy in the driving force for electron injection after photoexcitation and dye regeneration, combined with interfacial charge recombination loss reactions (Figure ) . Therefore, it is strategically important to reduce energy losses as much as possible by optimization of efficient charge transfer reactions, improving DSSC performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, many newly developed D/A infrared dyes with small energy‐gaps based on CA acceptor have critical kinetic limitations such as low electron injection efficiency, which is probably induced by the short singlet excited‐state lifetimes of organic dyes . It has been demonstrated that the replacement of CA with more electron‐deficient unit benzothiadiazole‐benzoic acid (BTBA), can bring forth energy‐gap shrinkage concomitant with prolonged lifetime of excited‐state, which are highly desirable for more efficient DSCs.…”
Section: Introductionmentioning
confidence: 99%